Answer:
<em>f( g ( - 2 ) ) = - 14 </em>
Step-by-step explanation:
f(x) = - 2x + 4
g(x) = 3x² - x - 5
f( g ( - 2 ) ) = ?
g( - 2 ) = 3( - 2 )² - ( - 2 ) - 5 = 12 + 2 - 5 = 9
f(9) = - 2 × 9 + 4 = - 14
<em>f( g ( - 2 ) ) = - 14</em>
Answer:
22 4/5 yards
Step-by-step explanation:
(7 3/5) x 3 = 22 4/5
Answer:
B
Step-by-step explanation:
Step-by-step explanation:
The scale factor is 12/6 = 10/5 = 2.
X is equal 3. to do this, you do reverse of order of operations. So this means that you would to the 'times 2' first by dividing 4 by 2 to make it 2. then, in the parenthesis, since there is a 'minus 1', therefore you are going to add 1+2 which equals three. <span />